Strategies to Improve the World Food Programme's Revenue Mobilisation and Procurement Practices. (12th April 2013) - Ramachandran, Vijaya; Leo, Benjamin; McCarthy, Owen
<x xml:space="preserve">Abstract</x> Currently, a vast majority of WFP food procurement is executed through spot markets, which exposes it to substantial commodity and transport price risk as well as significant delays in delivery. The WFP also has limited flexibility owing to unpredictable revenue mobilisation, partly driven by restricted donor contributions. However, a significant portion of its operations are fairly predictable – both in terms of countries and delivery volumes. There are several types of derivatives contracts available at commodities exchanges that can facilitate strategic hedging. Greater commitments of untied cash donations from the US and other major donors can give the WFP significant operational flexibility to execute prudent financial management operations without damaging local food markets.